(untitled) (Conference on English Language Teaching, 2023)
Anggaraini, S & A. Damanhuri.2017. Language Feature of Wmen‟s Responses toward Justin Bieber‟s Instagram Post. Language Horizon, 1 (1): 50-57 Brown, P., dan Levinson, S. (1987). Politeness Some Universals in Language Usage. Cambridge University Press. Choyimah, Nurul. 2015. Utterances and their Meanings. Tulungagung: IAIN Tulungagung Press. Griffin, E. (2012). A First Look At Communication Theory: eight edition. New York: McGraw-Hill. Harwood, C. 2017. “Politeness and University Student Online Communication”. Journal of the Faculty of Foreign Studies, 35-45. https://doi.org/https://doi.org/10.34050/els- jish.v1i1.4043 Kamsali, I. (2017). The Positive Politeness in Conversation performed by The Students of English Study Program of Timor University. Journal of Physical Chemistry B, 8(1), 28– 48. https://doi.org/https://doi.org/10.1016/S0009- 2614(00)00764-8 Kusno, A. (2015). Pematuhan dan Pelanggaran Prinsip Kesopanan Serta Fungsinya dalam Wacana Terkait Usulan Dana Aspirasi DPR di Rubrik Politik Kompasiana. Widyaparwa, 43(1), 65–78. https://doi.org/https://doi.org/10.26499/ wdprw.v43i1.106 Kusno, A., & Rahman, A. (2016). BentukBentuk Pelanggaran Prinsip Kesopanan dalam Ceramah Keagamaan. LiNGUA: Jurnal Ilmu Bahasa Dan Sastra, 11(2), 103–115. https://doi.org/10.18860/ling.v11i2.350 Lakoff, R. (1972). Language in Context. Linguistic Society of America. Mansoor, I. K. (2018). Politeness: Linguistic Study. International Journal of Research in Social Sciences and Humanities. 8(4), 167-179 Norra Maros, M. & L. Rosli.2017. “Politeness Strategies in Twitter Updates of Female Language Studies Malaysian Undergraduates”. The Southeast Asian Journal of English Language Studies,23(1): 132-14 Mukhtar. (2013). Metode Praktis Penelitian Deskriptif Kualitatif. Referensi (GP Press Group). Shanthi & Karappan. 2016. Communicative Patterns and Politeness Strategies in „SMS Your Views‟ Column in A Local English Daily. Dissertation. Kuala Lumpur: Master of English As Second Language Program Spencer-Oatey, H. (2000). Culturally Speaking: Culture, Communication, and Human Behavior Journal Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Alfabeta, CV. https://massugiyantojambi.wordpress.com/2011/04/15/teori-motivasi/ Tamrin. (2014). Kesantunan Berbahasa Bugis pada Masyarakat Bugis di Kabupaten Sinjai Provinsi Sulawesi Selatan. Multilingual, 13(2), 208–218. Wardhaugh, R. (2006). An Introduction to Sociolinguistics FIFTH EDITION. Blackwell Publishing. Widhiarso, W. (2005). Pengaruh Bahasa Terhadap Pikiran: Kajian Hipotesis Benyamin Whorf dan Edward Sapir. Bahasa dan Pikiran Yetty. (2018). Politeness Strategy on Social Interaction Used by Munanese. ELS Journal on Interdisciplinary Studies in Humanities, 1(1), 59. Yule, G. (2014). Pragmatik. Pustaka Pelajar